Correction: Targeted Isolation of Antibodies Directed against Major Sites of SIV Env Vulnerability. - Rosemarie D Mason; Hugh C Welles; Cameron Adams; Bimal K Chakrabarti; Jason Gorman; Tongqing Zhou; Richard Nguyen; Sijy O'Dell; Sabrina Lusvarghi; Carole A Bewley; Hui Li; George M Shaw; et al. (PLoS Pathogens)
[This corrects the article DOI: 10.1371/journal.ppat.1005537.].